2010
DOI: 10.1161/strokeaha.109.569269
|View full text |Cite|
|
Sign up to set email alerts
|

Length of Stay and Total Hospital Charges of Clipping Versus Coiling for Ruptured and Unruptured Adult Cerebral Aneurysms in the Nationwide Inpatient Sample Database 2002 to 2006

Abstract: Background and Purpose-We have previously reported the difference in length of stay and hospital charges for patients with cerebral aneurysms treated with either clipping or coiling at our institution. We now report an analysis of the same comparison at a national level conducted using the Nationwide Inpatient Sample database. hospitalizations for unruptured aneurysm treatments (4700 clipping, 4699 coiling). For ruptured aneurysm patients, after adjusting for the effects of patient-specific and hospital-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 12 publications
10
82
2
9
Order By: Relevance
“…These previous studies do not corroborate what we observe clinically. In humans, aneurysms occur more often in women (70–75%) pre‐ and postmenopause 2. However, aneurysm ruptures occur most often in postmenopausal women 3, 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies do not corroborate what we observe clinically. In humans, aneurysms occur more often in women (70–75%) pre‐ and postmenopause 2. However, aneurysm ruptures occur most often in postmenopausal women 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen deficiency has been linked to aneurysm formation and rupture. Approximately 70% to 75% of aneurysms occur in women,2 with postmenopausal women having the highest risk for aneurysm rupture 3, 4. Several studies have investigated estrogen deficiency and CA5, 6, 7, 8; however, the mechanism remains unknown.…”
mentioning
confidence: 99%
“…Coiling was associated with significantly shorter lengths of hospital stay and significantly lower total hospital charges for patients with both ruptured and unruptured aneurysms, compared with clipping. 19 One-stage coiling of multiple aneurysms may further shorten the lengths of overall hospital stays and reduce overall total medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…Hoh et al 4 reported the cost of cerebral aneurysm treatment in a previous study using NIS data, showing that clipping was associated with significantly longer stay and significantly higher total hospital charges than coiling for patients with both ruptured and unruptured aneurysms. We sought to delineate further the reasons for cost differentials in unruptured aneurysms by stratifying patients by age and outcome and by evaluating the trend in cost with time.…”
Section: Discussionmentioning
confidence: 99%